Reproducibility of Automated Breast Ultrasonography and Handheld Ultrasonography for Breast Lesion Size Measurement. Issue 1 (10th March 2022) - Park, Ko Woon; Ko, Eun Young; Park, Surin; Han, Boo-Kyung; Ko, Eun Sook; Choi, Ji Soo; Kwon, Mi-ri
Abstract: The purpose of our study was to evaluate the reproducibility of size measurement of breast lesions using automated breast ultrasonography (ABUS) compared with that with handheld ultrasonography (HHUS). Three breast radiologists performed HHUS and measured the lesions size in 2 different phantoms: lesions with various shape, size, and same stiffness (phantom 1) and lesions with same shape, size, and various stiffness (phantom 2). After 1 month, the same radiologists measured the lesion size of the same breast phantoms in the images obtained using ABUS. We evaluated interobserver variability between 3 radiologists in ABUS and HHUS, and intraobserver variability of radiologists between ABUS and HHUS. Intraclass correlation coefficient (ICC) was used in statistical analysis. The measured size of lesions on HHUS was slightly larger than that on ABUS in both phantom 1 and 2, although not statistically significant ( P = 0.314, P = 0.858). There were no significant differences in size measurements between the radiologists' measurements and the reference size in phantom 2 ( P = 0.862). The ICCs for the interobserver agreement between the 3 radiologists were 0.98 to 0.99 on ABUS and 0.99 to 1.00 on HHUS, respectively. The ICCs for the intraobserver agreement between ABUS and HHUS were 0.97 to 0.97 in phantom 1 and 0.98 to 0.99 in phantom 2. In conclusion, ABUS showed excellent interobserver and intraobserver agreement with HHUS in measuring size of the lesions, regardless of shape, size, and stiffness. Therefore, ABUS mixed with HHUS can be used reliably in following up breast lesions size.